Reconstructing identities amidst spatial transgression in Emily Brontë’s Wuthering Heights (1847) - Jujar Singh, Hardev Kaur; Zhixing, Nie (Universiti Putra Malaysia, 2025)
This study explores Emily Brontë’s Wuthering Heights (1847), a novel thoroughly examined through feminist, trauma, narratological, and psychoanalytic perspectives, especially concerning its enigmatic character, Heathcliff. However, the theme of spatial transgression as a crucial narrative element has received less attention. Applying Deleuze and Guattari’s notions of “striated space” and “smooth space” from A Thousand Plateaus (1980), this paper investigates the spatial dynamics within Wuthering Heights. It uncovers how the restrictive environments of Wuthering Heights and Thrushcross Grange and patriarchal and religious constraints confine Catherine and Heathcliff within “striated space.” Brontë contrasts detention and freedom, confinement and mobility, and oppression and liberation to highlight this binary opposition. This study reveals the complex interplay between “striated space” and “smooth space”, and their significant impact on Catherine and Heathcliff’s identities. It particularly examines how themes of “flight,” “nomadism,” and “becoming” are woven into the narrative, illustrating the characters’ struggles with identity crises and their processes of identity reconstruction.